Energy Harvesting-Based Transmission Schemes in Cognitive Radio Networks with a Power Beacon - Nguyen, Anh Tuan; Nguyen, Toan Van (Old Journal, 2020)
Energy harvesting is emerged as a promising technique to solve the energy constraint problem of wireless communications networks. In this paper, new energy harvesting-based transmission schemes are proposed to improve the outage probability and throughput in underlay cognitive radio networks. In this system, a secondary source can harvest energy from a power beacon (PB) and/or a primary transmitter (PT) to transmit data to a secondary destination in the presence of a primary receiver. Particularly, we propose the BS, TS and SBT schemes to improve system performance. The BS scheme tries to harvest energy from the PB while the TS scheme harvests energy only from the PT. In the SBT scheme, the energy harvested from both PB and PT is used for data transmission. For performance evaluation, we derive the exact closed-form expressions for the outage probability and throughput of the proposed schemes over Rayleigh fading channels, which are later verified by Monte Carlo simulations.